Keeping Up with the Jansens: Causal Peer Effects on Household Spending, Beliefs and Happiness - Maarten van Rooij; Olivier Coibion; Dimitris Georgarakos; Bernardo Candia; Yuriy Gorodnichenko (Institute of Labor Economics (IZA), 2024)
How strong are peer effects on the beliefs and spending decisions of individuals? We use a randomized control study in which treated households are told about either average income or debt of individuals like them to assess how peer effects influence their beliefs and spending. The information treatments are successful at moving respondents' beliefs about peers' incomes and debt levels. We find that individuals with exogenously higher perceived relative income become more opposed to redistribution and increase the amount of time they spend socializing with peers. In addition, we find some evidence of reallocative "keeping up with the Joneses" on spending, as those who learn their peers earn more than they thought tend to reallocate their spending toward durable goods and away from non-durables. However, the quantitative magnitude of peer effects on spending is small in the months following the information experiment. Peer effects also matter for labor supply decisions and ex-post employment outcomes. Finally, believing that one earns more than peers causally leads to large positive effects on happiness, above and beyond effects coming from spending more time with peers, changing beliefs about redistribution, or changes in spending patterns.
Keywords: D3; D6; D1; E21; 330; peer effects; surveys